(untitled) (Sciences & Technology. A, exactes sciences, 2002)
This paper present the applications of the fast Fourier transform (FFT) and the continuous wavelet transform (CWT) to analyse the normal and pathological cases of the phonocardiogram signals (PCG). The wavelet transform provides more features of the PCG signals that will help physicians to obtain qualitative and quantitative measurements of the time-frequency PCG signal characteristics. The frequency content of such a signal is shown to be determined by the FFT without difficulties.